Evaluation of poly(L-lactic acid) (PLLA) rapid indicator film on deterioration degree of Refined, Bleached and Deodorised Malaysian Tenera palm olein oil (RBDPO) during long-term repetitive deep-fat frying - Saiful Irwan Zubairi; Ili Afiqa Ab Kadir; Zainun Nurzahim; Azwan Lazim (Arabian Journal of Chemistry, 2022)
Palm olein oil is widely used as a medium for deep-frying purposes in the domestic and commercial sectors. However, repetitive usage beyond the recommended cycle leads to significant deterioration and spoilage of the oil. Therefore, this research investigated the effect of long-term repetitive deep-fat frying on the physicochemical properties of Refined, Bleached and Deodorised Malaysian Tenera Palm Olein oil (RBDPO) as well as the suitability of poly(L-lactic acid) (PLLA) film as a potential rapid indicator to determine the spoilage level of recycled palm olein oil. The study was carried out using three different RBDPO conditions; RBDPO without potatoes (RBDPO-1), RBDPO with potatoes (RBDPO-2), and RBDPO with Afdhal Oil (AO, an oil additive chemical) and potatoes (RBDPO-3). The deep-frying process was performed for 15 mins at 180 ± 5 °C for 15 cycles. Based on the results, the oil temperature fluctuation during the frying process was insignificant for every cycle (p > 0.05). After 15 frying cycles, all oil samples demonstrated a considerably altered and deteriorated composition, both physically and chemically. The comparison between the 1st and 15th frying cycles showed a significant difference (p < 0.05) in the decrease of moisture content and contact angle. Furthermore, the redness colour and viscosity for RBDPO-1, RBDPO-2 and RBDPO-3 increased significantly. The RBDPO-2 recorded the highest value for moisture content, contact angle, colour and viscosity after 15 frying cycles with 30.40 ± 0.2%, 26.01 ± 0.02°, 10.77 ± 0.15 Lovibond, and 133.5 ± 0.2 cP, respectively. However, the density value was insignificant (p > 0.05) between the 1st and 15th frying cycles for all types of oil. Besides, the peroxides value (PV) was steadily increased within the safety limit of Food Act (1983) (Laws of Malaysia: Act 281), with the aldehyde (CO) functional group was detected in all oil samples throughout the 15 frying cycles. Hence, the high correlation between the contact angle and all parameters except density showed that contact angle analysis using PLLA film was a suitable technique for rapid oil spoilage indicator model.